2011
DOI: 10.1039/c0cp01479f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and dynamics of Mg(ND3)6Cl2

Abstract: The crystal structure and dynamics of Mg(ND(3))(6)Cl(2) have been investigated by powder neutron diffraction and molecular dynamics. The powder diffraction data can be well described by 4 partly occupied deuterium sites in a square arrangement around the N atoms, which is seemingly inconsistent with the 3-fold symmetry of the ND(3) molecule. Molecular dynamics show highly correlated rotational and translational motion of the ND(3) molecules which explains the apparent 4-fold symmetry of the deuterium arrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…For Mg(ND 3 ) 6 Cl 2 , Sørby et al reported that the ND 3 molecules in ammine complex phase has highly correlated rotational and translational motions. 19 Thus, it is expected that the degree-of-freedom of NH 3 molecule in Mg(NH 3 )Cl 2 is extremely high. Form the ΔS 0 obtained in this work, the entropy of solid at standard conditions of Mg(NH 3 ) 6 Cl 2 and Mg(NH 3 )Cl 2 were estimated to be S 0 = 352 and 185 J/mol K, respectively (Table S1), 20 where the S 0 per NH 3 of Mg(NH 3 ) 6 Cl 2 and Mg(NH 3 )Cl 2 was described as 59 and 185 J/mol K, respectivaly.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For Mg(ND 3 ) 6 Cl 2 , Sørby et al reported that the ND 3 molecules in ammine complex phase has highly correlated rotational and translational motions. 19 Thus, it is expected that the degree-of-freedom of NH 3 molecule in Mg(NH 3 )Cl 2 is extremely high. Form the ΔS 0 obtained in this work, the entropy of solid at standard conditions of Mg(NH 3 ) 6 Cl 2 and Mg(NH 3 )Cl 2 were estimated to be S 0 = 352 and 185 J/mol K, respectively (Table S1), 20 where the S 0 per NH 3 of Mg(NH 3 ) 6 Cl 2 and Mg(NH 3 )Cl 2 was described as 59 and 185 J/mol K, respectivaly.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a promising candidate material for hydrogen storage, the Mg(NH 3 ) 6 Cl 2 compound has been extensively studied by experimental researchers in recent years. [37][38][39][40] On the basis of its crystal structure, 41 three conformations of the isolated Mg(NH 3 ) 6 Cl 2 molecule were obtained. The resulting geometric structures are depicted in Fig.…”
Section: Equilibrium Geometriesmentioning
confidence: 99%
“…35,36 Nevertheless, Mg(NH 3 ) 6 can be obtained under the existence of Cl À counterions in Mg(NH 3 ) 6 Cl 2 . [37][38][39][40][41] Based on the definition of alkalide, it is interesting to replace one or two Cl À in Mg(NH 3 ) 6 Cl 2 with alkali metal atoms to detect whether novel inorganic Mg-based alkalides can be obtained or not. As for Ca(NH 3 ) 6 , the valence electrons of Ca are pushed out by NH 3 complexants, and delocalized outside the whole structure (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…41 Nevertheless, with the existence of Cl À counterions, Mg(NH 3 ) 6 Cl 2 can be obtained. [42][43][44][45][46] Li's group 35 used M(NH 3 ) 6 (M ¼ Mg, Ca) to theoretically design a series of novel alkalide molecules with double alkali anions M(NH 3 ) 6 Na 2 and they found that those compounds had large static rst hyperpolarizability (electronic contribution b e 0 ) values ranging from 0 to 1.23 Â 10 5 (a.u.). It was noticed that one of the isomers with centrosymmetry (with D 3d point group) of M(NH 3 ) 6 Na 2 was the most stable, but its b e 0 value was zero.…”
Section: Introductionmentioning
confidence: 99%